Wetting characteristics of Sn-5Sb-CuNiAg lead-free solders on the copper substrate. Issue 2 (23rd August 2021) - Wang, Xiuqi; Sun, Fenglian; Han, Bangyao; Cao, Yilun; Du, Jinyang; Shao, Long; Liu, Guohuai
Abstract : Purpose: The purpose of this paper is to investigate the wetting behaviors of Sn-5Sb-CuNiAg solders on copper substrates in different soldering processes and the effects of alloying elements on the wettability. Design/methodology/approach: Sn-5Sb-CuNiAg solder balls (750 µm in diameter) were spread and wetted on 40 × 40 × 1 mm copper plates, in different fluxes, soldering temperatures and time. The contact angles were obtained by a home-made measuring instrument. The samples were polished and deep etched before analyzed by scanning electron microscopy. Energy dispersive X-ray spectroscopy was used to identify the composition of the joints. Findings: The effects of different soldering processes and alloying elements on the wetting behaviors of Sn-5Sb-CuNiAg solders on copper substrates were calculated and expounded. The rosin-based flux could effectively remove oxidation layers and improve the wettability of Sn-5Sb-CuNiAg solders. Then with the increase of soldering temperature and time, the contact angles decreased gradually. The soldering processes suited for Sn-5Sb-CuNiAg solders were RMA218, 280°C and 30 s. Considered the effects of alloying elements, the wettability of Sn-5Sb-0.5Cu-0.1Ni-0.5Ag was relatively favorable on copper substrates. Besides, Ni could accumulate at the solder/Cu interface and form a jagged (Cu, Ni)6Sn5 IMC. Originality/value: This work was carried out with our handmade experiment equipment and the production of the quinary lead-free solder alloy used in wetting tests belongs to us. The investigated Sn-5Sb-CuNiAg alloys exhibited higher melting point and preferable wettability, that was one of the candidates for high-temperature lead-free solders to replace high-Pb solders, and applied extremely to high temperature and frequency working environments of the third-generation semiconductors components, with a greater potential research and development value.